1996
DOI: 10.1007/bf02252938
|View full text |Cite
|
Sign up to set email alerts
|

Determination of bradykinin-(1–5) in inflammatory exudate by a new ELISA as a reliable indicator of bradykinin generation

Abstract: We have developed an ELISA for BK-(1-5) (Arg1-Pro2-Pro3-Gly4-Phe5). In rat carrageenin-induced pleurisy, in which a plasma exudation peak was observed 5 h after carrageenin, BK levels in the exudates were negligible (< 60 pg/rat). BK-(1-7) (des-Phe8-Arg9-BK) was detectable (900-400 pg/rat) over the entire course of the inflammation. However, a larger amount of BK-(1-5) was detectable in association with the increase in plasma exudation, showing a peak (8800 +/- 1200 pg/rat) 3 h after carrageenin. Bromelain (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 22 publications
0
24
0
1
Order By: Relevance
“…Collectively, these data demonstrated that exogenous bradykinin prevented deep vein thrombosis via reduced monocytes and HUVECs TF expression and adhesion of leukocytes to the endothelium. Furthermore, the angiotensin-converting enzyme breakdown product of bradykinin, Arg-Pro-Pro-Gly-Phe (RPPGF), is a stable metabolite of bradykinin [35,36], and this peptide has biological activity [37]. Further study indicated that RPPGF inhibited both α-and β-thrombin-induced platelet aggregation and secretion via binding to the active site of thrombin and the extracellular domain of PAR1 to prevent thrombin cleavage after Arg41 [18,38].…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these data demonstrated that exogenous bradykinin prevented deep vein thrombosis via reduced monocytes and HUVECs TF expression and adhesion of leukocytes to the endothelium. Furthermore, the angiotensin-converting enzyme breakdown product of bradykinin, Arg-Pro-Pro-Gly-Phe (RPPGF), is a stable metabolite of bradykinin [35,36], and this peptide has biological activity [37]. Further study indicated that RPPGF inhibited both α-and β-thrombin-induced platelet aggregation and secretion via binding to the active site of thrombin and the extracellular domain of PAR1 to prevent thrombin cleavage after Arg41 [18,38].…”
Section: Discussionmentioning
confidence: 99%
“…bromelain had activity similar to 0.3 mg/kg i.p. dexamethasone (equivalent to 20 mg prednisone in a 70-kg human) in rat pleurisy models [11,12]. Bromelain had efficacy similar to or better than classic non-steroidal antiinflammatory agents (NSAIDs) in some rheumatologic studies in humans [14,16,19].…”
Section: Introductionmentioning
confidence: 99%
“…These include the experimental allergic encephalomyelitis (EAE) model of the human autoimmune disease multiple sclerosis (3), carrageenan-induced pleurisy in the rat (4)(5)(6), immunologically mediated arteriosclerosis in rat aortic allografts (7), rheumatologic diseases in mice and humans (8)(9)(10)(11)(12)(13), and allergic asthma (14) and rhinitis (15). Some studies demonstrated that bromelain had efficacy similar to standard anti-inflammatory drugs such as dexamethasone (5,6) or non-steroidal anti-inflammatory agents (NSAIDs) (8,10,11,16). Our previous studies showed that oral administration of 5 mg bromelain/day markedly decreased the development and severity of inflammatory bowel disease in IL-10 −/− mice (17).…”
Section: Introductionmentioning
confidence: 99%